Mitochondrial genome modulates myocardial Akt/Glut/HK salvage pathway in spontaneously hypertensive rats adapted to chronic hypoxia - Nedvedova, Iveta; Kolar, David; Elsnicova, Barbara; Hornikova, Daniela; Novotny, Jiri; Kalous, Martin; Pravenec, Michal; Neckar, Jan; Kolar, Frantisek; Zurmanova, Jitka M (Physiological genomics, 2018)
Recently we have shown that adaptation to continuous normobaric hypoxia (CNH) decreases myocardial ischemia/reperfusion injury in spontaneously hypertensive rats (SHR) and in a conplastic strain (SHR-mtBN). The protective effect was stronger in the latter group characterized by a selective replacement of the SHR mitochondrial genome with that of a more ischemia-resistant Brown Norway strain. The aim of the present study was to examine the possible involvement of the hypoxia inducible factor (HIF)-dependent pathway of the protein kinase B/glucose transporters/hexokinase (Akt/GLUT/HK) in this mitochondrial genome-related difference of the cardioprotective phenotype. Adult male rats were exposed for 3 wk to CNH ([Formula: see text] 0.1). The expression of dominant isoforms of Akt, GLUT, and HK in left ventricular myocardium was determined by real-time RT-PCR and Western blotting. Subcellular localization of GLUTs was assessed by quantitative immunofluorescence. Whereas adaptation to hypoxia markedly upregulated protein expression of HK2, GLUT1, and GLUT4 in both rat strains, Akt2 protein level was significantly increased in SHR-mtBN only. Interestingly, a higher content of HK2 was revealed in the sarcoplasmic reticulum-enriched fraction in SHR-mtBN after CNH. The increased activity of HK determined in the mitochondrial fraction after CNH in both strains suggested an increase of HK association with mitochondria. Interestingly, HIF1a mRNA increased and HIF2a mRNA decreased after CNH, the former effect being more pronounced in SHR-mtBN than in SHR. Pleiotropic effects of upregulated Akt2 along with HK translocation to mitochondria and mitochondria-associated membranes can potentially contribute to a stronger CNH-afforded cardioprotection in SHR-mtBN compared with progenitor SHR.
Keywords: signální transdukce; Signal Transduction; Hexokinase; druhová specificita; genom mitochondriální; Hypertension; Adaptation, Physiological; potkani inbrední BN; Mitochondria, Heart; Hypoxia-Inducible Factor 1; Genome, Mitochondrial; srdeční mitochondrie; Hypoxia; zvířata; faktor 1 indukovatelný hypoxií; cardioprotection; proteiny usnadňující transport glukosy; hypoxie; Rats, Inbred BN; protoonkogenní proteiny c-akt; Glucose Transport Proteins, Facilitative; Proto-Oncogene Proteins c-akt; Male; potkani inbrední SHR; hypertenze; hexokinasa; Species Specificity; Akt pathway; fyziologická adaptace; hypoxia; myokard; Animals; SHR strains; Myocardium; mužské pohlaví; Rats, Inbred SHR; mitochondrial genome